EMPOWERMENT OF THE JANGGALA VILLAGE TP PKK THROUGH TRAINING IN SEWING, ENTREPRENEURSHIP, FINANCIAL MANAGEMENT, AND BATIK PRODUCT DIVERSIFICATION - Hartono, Rudi; Fadilah, Mohamad Fazar; Awaludin, Adila; Asnani, Ari; Dwiasi, Dian Windy; Adawiyah, Wiwiek Rabiatul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Janggala Village in Tasikmalaya Regency is designated as a national priority area characterized by relatively high poverty rates and susceptibility to natural disasters. As a strategic community group, the Family Welfare Empowerment Team (TP PKK) of Janggala Village encounters significant challenges, specifically low entrepreneurial skills, limited access to production equipment, and weak business management governance. This empowerment program aims to enhance the partners' economic independence by strengthening production capabilities (hard skills) and business management competencies (soft skills). The implementation method utilized a participatory "learning by doing" approach combined with intensive mentoring, which encompassed training in sewing batik derivative products, entrepreneurship management assistance, financial recording workshops, and the facilitation of appropriate technology. Evaluation results indicated a significant improvement in partner empowerment. In the managerial aspect, entrepreneurial understanding increased by 32.2% (reaching 88.4%), and financial recording proficiency rose by 32% (reaching 87.8%). Regarding technical aspects, sewing skills improved by 27% (reaching 83.6%). Furthermore, the program successfully facilitated the provision of production equipment, including sewing and overlock machines, enabling 35 TP PKK members to manufacture ready-to-use products such as tote bags, pouches, and outerwear.